Vulnerability and economic deficiency in consumer existentialist contracts - Goiabeira Rosa, Luiz Carlos (2017)
This research summarizes the concepts of vulnerability and economic deficiency within the context of consumer protection. Furthermore, this study also addresses the expansion and maximization of the contractual parties in these contracts, which has commodity as its essential object. From using deductive reasoning and the comparative method, this research explains vulnerability and its species; questions whether economic deficiency is another form of consumer fragility in the legal procedural framework; and considers the importance of diminishing consumer vulnerability and economic deficiency as a means for protecting consumers.